A Review of Deep Multi-Objective Reinforcement Learning and Vision-Based Systems for Smart Cities - Alharbi, Saad (Informatica, 2025)
Smart cities leverage artificial intelligence to address urban challenges such as traffic congestion, environmental sustainability, public safety, and energy efficiency. Among AI techniques, the integration of multi-objective reinforcement learning (MORL) and computer vision (CV) offers adaptive, real-time decision-making capabilities while processing complex visual data streams. This paper presents a comprehensive review of the joint application of MORL and CV in smart city environments. A systematic search was conducted across six major databases (Scopus, Web of Science, IEEE, Springer, MDPI, and Elsevier) from 2019 to 2024, resulting in the selection of 90 relevant studies. The review follows a thematic analysis approach, categorizing the literature into smart mobility, infrastructure, environment, governance, and smart living. Key findings indicate that multi-agent MORL and CV are increasingly used in traffic signal control, autonomous vehicle navigation, energy management, surveillance, healthcare, and waste management. However, despite advancements in deep RL algorithms like DDPG, PPO, SAC, and advanced CV techniques such as semantic segmentation and multi-camera tracking, the direct integration of these technologies remains underexplored in many domains. The paper highlights current research gaps, including the lack of standardized frameworks for MORL-CV synergy, scalability limitations, ethical concerns, and insufficient quantitative benchmarking across studies. Additionally, trends such as federated learning, edge computing, and digital twins are identified as promising enablers for future MORL-CV solutions in urban contexts. This review serves as a resource for researchers and policymakers aiming to develop sustainable and intelligent urban systems by bridging perception (via CV) with adaptive control (via MORL) for real-time, multi-criteria decision support.